Postdischarge service utilisation and outcomes among Chinese and South Asian psychiatric inpatients in Ontario, Canada: a population-based cohort study. Issue 1 (13th January 2018) - Chiu, Maria; Gatov, Evgenia; Zaheer, Juveria; Lebenbaum, Michael; Fu, Longdi; Newman, Alice; Kurdyak, Paul
Abstract : Objective: We sought to examine the short-term and long-term impacts of psychiatric hospitalisations among patients of Chinese and South Asian origin. Design: Retrospective population-based cohort study using linked health administrative data. Setting: We examined all adult psychiatric inpatients discharged between 1 April 2006 and 31 March 2014 in Ontario, Canada, who were classified as Chinese, South Asian and all other ethnicities (ie, 'general population') using a validated algorithm. We identified 2552 Chinese, 2439 South Asian and 127 142 general population patients. Primary and secondary outcome measures: We examined psychiatric severity measures at admission and discharge and performed multivariable logistic regression analyses to examine 30-day, 180-day and 365-day postdischarge service utilisation and outcomes, comparing each of the ethnic groups with the reference population, after adjustment for age, sex, income, education, marital status, immigration status, community size and discharge diagnosis. Results: Despite presenting to hospital with greater illness severity, Asian psychiatric inpatients had shorter lengths of hospital stay and greater absolute improvements in mental health and functional status at discharge compared with other inpatients. After hospitalisation, Chinese patients were more likely to visit psychiatrists and South Asian patients were more likely to seek mental healthcare from general practitioners. They were also less likely to have a psychiatric readmission or die 1 year following hospitalisation (adjusted ORChinese =0.87; 95% CI 0.79 to 0.97; adjusted ORSouth Asian =0.82, 95% CI 0.73 to 0.91). Findings were consistent across genders, psychiatric diagnoses and immigrant groups. Conclusion: Once hospitalised, patients of Chinese and South Asian origin fared as well as or better than general population patients at discharge and following discharge, and had a positive trajectory of psychiatric service utilisation.